The Relationship between Vocabulary Mastery, Content Schemata and Reading Comprehension - Soraya, Kety; Ramdani, Dely (JEDLISH : Journal Of Education and English Language Teaching, 2022)
Recently there has been a great debate among the educators which one dominates between vocabulary mastery and content schemata to improve students’ reading comprehension. to counter this issue, this present study tries to investigate whether the combination of vocabulary mastery and content schemata are significantly related to reading comprehension, whether there is a significant relationship between vocabulary mastery and reading comprehension while content schemata is held constant, and whether there is a significant relationship between content schemata and reading comprehension while vocabulary is held constant. The writer used two stages sampling technique. Two-stage random sampling is combination of cluster random sampling with individual random sampling. Therefore, 54 students out of 216 students of the eighth grade in academic year 2013/2014 were chosen. The method of the research was a correlation study. Two types of research instruments were used to collect the data. They were multiple-choice tests and questionnaire. Then the data were analyzed by multiple correlations and multiple regressions. Based on the results of the data analysis, there were three conclusions drawn: first, the combination of vocabulary mastery (X1) and content schemata (X2) are jointly related to reading comprehension (Y). Second, there is a significant relationship between vocabulary mastery(X1) and reading comprehension (Y). Third, there is a significant relationship between the content schemata (X2) and reading comprehension (Y). Based on the finding of the three test hypotheses, it was found that the test estimated regression equation on content schemata is higher than vocabulary mastery. It means that students with minimum vocabulary mastery can still comprehend a text with an appropriate content schema.